Students Learning Attitude Doing Online Learning During The Covid-19 Pandemic At PKK Culinary Education Study Program - Sunaringwardani, Shinta Safitri; Elida, Elida (Universitas Negeri Padang, 2022)
This research started from a problem that the authors found in the pre-research about the learning attitudes of students doing online learning during the COVID-19 pandemic. A positive learning attitude can support online learning activities. However, there is still a lack of student awareness about the importance of applying a positive learning attitude to online learning. The purpose of this research is to describe how students' learning attitudes take part in online learning during the COVID-19 pandemic in the PKK Study Program Concentration of Culinary Education. This type of research is descriptive with a quantitative approach. The population in this study were 198 students of the PKK Concentration of Culinary Education in 2019 and 2020 a sample of 66 people was taken using the Random Sampling method. The data collection technique was carried out using a questionnaire using a Likert scale that had been tested for validity and reliability. Furthermore, the data were analyzed descriptively with classification techniques.The results showed that the learning attitude of students participating in online learning in the PKK Study Program Concentration of Culinary Education as a whole was categorized as positive with a frequency of 34 respondents.